2014
DOI: 10.1080/13102818.2014.909152
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous spermine pretreatment confers tolerance to combined high-temperature and drought stressin vitroin trifoliate orange seedlings via modulation of antioxidative capacity and expression of stress-related genes

Abstract: Spermine (Spm) is thought to play an important role in drought or high-temperature (HT) tolerance. However, it is not clear whether Spm confers similar resistance in the presence of both drought and HT, which often occur simultaneously. In the present study, the trifoliate orange (Poncirus trifoliata (L.) Raf.) seedlings were pretreated with 1 mmol L−1 Spm to evaluate their tolerance to combined drought and HT (45 ºC) stress. Spm-pretreated seedlings showed less leaf wilting, less water loss and less electroly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 36 publications
5
34
0
1
Order By: Relevance
“…Based on the data shown in this study, the inoculation with BOFC15 increased plant drought resistance, which contributed to the effects caused by microbe-induced increase in cellular PAs, including improved root systems, enhanced antioxidant enzymatic activities, and increased ABA content. These observations were consistent with the results reported by previous studies; in particular, high PA levels can directly promote root growth [ 34 ] and up-regulate antioxidant enzymatic activities under stress conditions [ 40 , 41 , 42 ]. Moreover, the inoculated plants exhibited higher ABA contents than the control plants under DS conditions.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Based on the data shown in this study, the inoculation with BOFC15 increased plant drought resistance, which contributed to the effects caused by microbe-induced increase in cellular PAs, including improved root systems, enhanced antioxidant enzymatic activities, and increased ABA content. These observations were consistent with the results reported by previous studies; in particular, high PA levels can directly promote root growth [ 34 ] and up-regulate antioxidant enzymatic activities under stress conditions [ 40 , 41 , 42 ]. Moreover, the inoculated plants exhibited higher ABA contents than the control plants under DS conditions.…”
Section: Discussionsupporting
confidence: 93%
“…A recent study has reported that PAs can form complexes with SOD, GPX, and CAT, for which these enzymes function more efficiently compared with their isolated enzymes [ 41 ]. Moreover, exogenous PAs have been shown to enhance the activities of antioxidant enzymes such as SOD and CAT under abiotic stress conditions [ 16 , 17 , 42 ]. Hence, BOFC15 mitigated drought-induced oxidative damage to plant cells via the activation of antioxidant systems, thereby regulating the ROS generation and redox status.…”
Section: Discussionmentioning
confidence: 99%
“…Abscisic acid-responsive element binding factors (ABFs) are basic region/leucine zipper (bZIP) class transcription factors involved in the transcriptional regulation of abscisic acid-and/or stress-responsive genes via interaction with ABRE cis elements in their promoters. Trifoliate orange seedlings pre-treated with spermine had significantly higher expression of genes for heat shock proteins and ABFs than the control plants both under normal conditions and during combined drought and heat treatment [39]. Spermine has also been shown to induce certain enzymes, such as woundinduced protein kinase, and to be responsible for the post-translational activation of certain mitogen-activated protein kinases, such as salicylic acid-induced protein kinase.…”
Section: Sperminementioning
confidence: 99%
“…Citrus is most often grown in warm climates with well-drained soils in areas that are subject to water deficit and that often require supplemental irrigation (Syvertsen & Garcia-Sanchez, 2014). Drought stress is an important feature in areas of citrus cultivation, including Spain (Gonzalez-Dugo et al, 2014), China (Fu et al, 2014), Australia (Staniford et al, 2009), South Africa (Dzikiti et al, 2011), and even Florida during autumn, and in cases of a relatively dry spring (Pérez-Pérez et al, 2007). Drought stress impacts citrus physiology by changing, for instance, amino acid and polyamine levels in leaves (Malik et al, 2014).…”
Section: Introductionmentioning
confidence: 99%